Meaning, mind, and matter philosophical essays - LePore, Ernest, 1950-; Loewer, Barry (Oxford : Oxford University Press, 2011)
Lepore and Loewer present a series of papers on three key ideas of philosophy: that a theory of meaning for a language is best understood as a theory of truth for that language; that thought and language are best understood together via a theory of interpretation; and that the mental is irreducible to the physical.
Description based on online resource; title from PDF title page (viewed on May 12, 2011).
Includes bibliographical references and index.
Keywords: Meaning (Philosophy); Philosophy of mind; Matter -- Philosophy